2019
DOI: 10.1177/2050313x18823380
|View full text |Cite
|
Sign up to set email alerts
|

Extensive unroofing of myocardial bridge: A case report and literature review

Abstract: Background:Myocardial bridge is defined as a segment of a coronary artery that takes an intramyocardial course. The presence of myocardial bridge has been observed in as many as 40%–80% of cases on autopsy, angiographically from 0.5% to 16.0%, and often asymptomatic. However, it has been associated with angina, coronary spasm, myocardial infarction, arrhythmias, syncope, sudden cardiac arrest, and death. Conflicting opinions exist on the timing of surgical intervention for myocardial bridge.Methods:We present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…A retrospective review of 31 patients who underwent surgical myotomy for significant MB has reported that all patients became symptom-free following the surgical procedure, with an improvement in the New York Heart Association class from I-III to I-II [ 9 ]. Our patient was very symptomatic and was treated medically for approximately six months.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review of 31 patients who underwent surgical myotomy for significant MB has reported that all patients became symptom-free following the surgical procedure, with an improvement in the New York Heart Association class from I-III to I-II [ 9 ]. Our patient was very symptomatic and was treated medically for approximately six months.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that in patients with severe bridging and concomitant CAD who are undergoing CABG, myotomy improves flow to branches proximal to the anastomosis and distal to the coronary arterial lesion [15-16]. Retrograde perfusion of the branches proximal to the distal anastomosis was visually obvious perioperatively while administrating of cardioplegic blood through the graft to the native coronary artery to evaluate flow, patency, and the integrity of the anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clinical features may manifest as angina-like chest pain, coronary spasm, acute coronary syndromes, left ventricular dysfunction, ventricular arrhythmias, and even sudden cardiac death. [42][43][44][45][46][47][48][49] Serious cardiac events are not common in the clinical setting. In addition, it is still arguable and uncertain whether MB can be directly attributable as the cause of the events.…”
Section: Clinical Features and Diagnostic Managementmentioning
confidence: 99%